Iatrogenic Effects of Orthodontic Treatment Decision-Making in Prevention, Diagnosis, and Treatment - Justus, Roberto (Springer International Publishing : Imprint: Springer, 2015)
This book is a well-illustrated, clearly written guide to the iatrogenic effects of orthodontic treatment that provides practical information on orthodontic diagnosis, treatment planning, and post-treatment retention and highlights preventive measures to avoid complaints and lawsuits. It is divided into three parts, focusing on white spot lesions, periodontal deterioration, and external apical root resorption (EARR). In the first part, the reader will learn how to minimize the risk of enamel decalcifications as a result of orthodontic treatment, and specifically how to deproteinize the enamel surface and bond brackets with hybrid glass ionomer cement. The second part, on prevention of periodontal deterioration, explains how to avoid lower incisor proclination and still achieve ideal long-term alignment and describes indications for different extractions. In the third part, the reader will learn why EARR occurs, how to apply strategies to minimize orthodontically induced EARR, and what to do when EARR is detected in timely fashion. Iatrogenic Effects of Orthodontic Treatment will be an excellent aid for both orthodontists and pediatric dentists.